Development and Evaluation of Phase Change Material-Enhanced Earthbag Buildings for Thermally Comfortable and Sustainable Temporary Housing in Nigeria: Numerical and Experimental Approach - Murtala Farouq, Mahmoud (2023)
Many developing countries face an increasing demand for affordable and sustainable housing, particularly for refugees and displaced communities that require temporary housing. However, there is a lack of research on the thermal comfort of such housing, which poses risks to vulnerable occupants, especially children. Existing studies on the thermal performance of shelters have predominantly focused on cold environments, neglecting hot climates, leaving this area of research underdeveloped. Earthbag buildings are promising options because of their low cost, sustainability, and ease of construction. However, indoor thermal comfort is often inadequate. This research aims to address this issue by developing and integrating phase change materials (PCM) into earthbag building to create a more comfortable living environment. The study began by fabricating earthbag blocks containing varying amounts of paraffin wax encapsulated in expanded perlite and graphite which was formed as PCM composite, to investigate the microstructural properties of the embedded PCM composite in soil, followed by testing the block thermal characteristics. Subsequently, an experimental analysis was conducted to understand the thermal properties of a wall embedded with optimum earthbag blocks. Two PCMs, namely A31 paraffin wax and Inertek26 powder microencapsulated, were incorporated into reduced-scale earthbag walls to create two distinct wall types: Wall-2_WA31 (a wall with A31 paraffin wax), and Wall-3_WInk26 (a wall with microencapsulated inertek26 powder). The performances of these PCM-integrated earthbag walls and Wall-1_baseline (a wall without PCM), were then monitored in an environmental chamber. To complement the experimental findings, a numerical model was developed using the EnergyPlus numerical simulation engine, employing the conduction finite difference (CondFD) approach and validated with experimental data. Through parametric analysis, the study identified the most effective PCM and the PCM supporting materials. Finally, a case study was presented, demonstrating the successful implementation of the optimum PCM-integrated earthbag walls (PCM-E wall) in a temporary housing unit in Maiduguri, Nigeria. This case study aimed to investigate the practical application and effectiveness of PCM-E wall in achieving optimal thermal comfort of temporary housing. The study revealed that the PCM and PCM composites exhibited favourable thermal stability, based on the Differential Scanning Calorimetry (DSC) and Thermogravimetric Analysis (TGA) tests. The Scanning Electron Microscope (SEM) results suggest that the PCM was evenly dispersed within the pores of the expanded perlite (EP) material at a 50% EP to PCM weight ratio. Moreover, the thermal performance results of the PCM-integrated earthbag blocks demonstrate that integrating PCM into earthbag block significantly moderates inner surface block wall temperatures by 1.2 to 4.1°C compared to the reference block. The integration of PCM into earthbag walls demonstrated remarkable improvements in thermal performance. Notably, the thermal conductivity of the earthbag walls significantly decreased with PCM incorporation, with Wall-3_WInk26 having achieved the lowest thermal conductivity at 0.43 W/mK. PCM-enhanced walls exhibited stable inner wall temperatures, with maximum reductions of 2.4°C compared to the baseline, and a substantial reduction in heat flux by up to 63.76%. The time lag in reaching the peak inner wall temperature increased by 3-5 hours, enhancing thermal comfort. The study identified an optimal PCM transition temperature of 31°C. Furthermore, PCM integration outperformed insulation alone, and increasing PCM and insulation layer thickness optimized thermal performance. A numerical model validated these findings, supporting the conclusion that PCMs enhanced thermal mass, reduced temperature fluctuations, and improved energy efficiency in earthbag construction. When combined with night ventilation strategies, PCM walls eliminated the need for air conditioning and maintained indoor temperatures within the comfort range of 23-32°C. In the long term, PCM-enhanced earthbag walls demonstrated significant thermal comfort improvements, with 94% comfort hours over the summer period. This research offered a promising solution for affordable, energy-efficient housing in hot climates using local earthen materials and passive cooling techniques.